Sex-Specific Pharmacotherapy for Migraine: A Narrative Review - Gazerani, Parisa; Cairns, Brian E. (Frontiers in Neuroscience, 2020)
Migraine is a common neurological disorder characterized by recurrent headache episodes that accompany sensory- motor disturbances, such as higher sensitivity to touch and light, extremity heaviness or weakness, and speech or language disabilities. Worldwide, migraine is one of the top ten causes of disability and hence poses a huge economic burden to society. On average, migraine occurs in 12% of population but its occurrence is sexually dimorphic, as it is two to three times more prevalent in women than in men. This female to male ratio of migraine prevalence is age- and sex hormone- dependent. Advancements in understanding migraine pathogenesis have also revealed an association with both genetics and epigenetics. The severity of migraine, in terms of its attack duration, headache intensity, frequency, and occurrence of migraine-associated symptoms, has generally been reported to be greater in women. Sex differences in migraine disability and comorbidities, such as psychiatric disorders, have also been noted in some population-based studies. However, research on sex-related differences in response to migraine treatments is relatively scarce. Although a general observation is that women consume more medication than men for migraine treatment, strategies for the use of abortive and preventive medications for migraine are generally similar in both sexes. This review summarizes available findings on sexually distinct responses to abortive and prophylactic pharmacotherapy of migraine. Basic experimental data and clinical findings will be presented, and potential mechanisms underlying sex-based responses will be discussed to highlight the importance and value of sex-based treatment in migraine research and practice.